Of rhizomes and pointillism: David john farmerʼs influence, method and art in the field. Issue 1 (1st March 2016) - Huff, Richard; Cors, Cynthia; Song, Jinzhou; Pang, Yali
Abstract : The work of David John Farmer has been recognized as critical to the Public Policy and Administration canon. Its impact has been far-reaching both geographically because of its international application and theoretically because of the vast array of public administration challenges it can help resolve. This paper uses the concepts of rhizomatic thinking and reflexive interpretation to describe Farmerʼs work. And because a critical piece of Farmerʼs work is a bridging of the gap between theory and practice, it formally introduces Farmerʼs research approach as Farmerʼs Method. This article is intended to serve as a useful tool for students, practitioners, and theorists in understanding the vast contributions of David John Farmer and the practical application of his work.